Pendampingan Pelaporan Keuangan BUMDes Berbasis Web - Savitri, Enni; Andreas, Andreas; Diyanto, Volta (Journal of Community Engagement Research for Sustainability, 2022)
BUMDes is an instrument to take advantage of the local economy with various types of potential. Utilization of this potential is primarily aimed at improving the economic welfare of the villagers through the development of economic enterprises. It is necessary to maximize the role of BUMDes to increase Village Original Income. The purpose of the service activity is to provide assistance in using the BUMDes simkeu application at BUMDes Berkah Bersama in Indragiri Hulu Regency so that it can increase village original income, strengthen the village economy and the welfare of rural communities. The implementation of this service uses a technique of assisting the application of the BUMDes business unit management system on the Web. Discussion and hands-on practice regarding BUMDes governance. The result of this activity is the simkeuBUMDes application. With this application, the BUMDes admin or manager is very helpful in managing BUMDes finances such as recapitulation of BUMDes Financial usage reports, member lists, member savings.